Examining multiracial youth in context: ethnic identity development and mental health outcomes - Fisher, Sycarah; Reynolds, Jennifer L.; Hsu, Wei-Wen; Barnes, Jessica; Tyler, Kenneth (My University, 2015)
Although multiracial individuals are the fastest growing population in the United States, research on the identity development of multiracial adolescents remains scant. This study explores the relationship between ethnic identity, its components (affirmation, exploration), and mental health outcomes (anxiety, depression) within the contexts of schools for multiracial adolescents. Participants were multiracial and monoracial minority and majority high school students (n=4,766). Using Analysis of Variance and Multiple Indicators Multiple Causes (MIMIC) models, results indicated that multiracial youth experience more exploration and less affirmation than African Americans, but more than Caucasians. In addition, multiracial youth were found to have higher levels of mental health issues than their monoracial minority and majority peers. Specifically, multiracial youth had higher levels of depression than their African American and Caucasian counterparts. Multiracial and Caucasian youth had similar levels of anxiety but these levels were significantly higher than African Americans. Results also show that school diversity can mitigate mental health outcomes finding that multiracial youth in more diverse schools are at lower risk for mental health issues.
Keywords: Ethnic identity; Multiracial adolescents; Anxiety; Depression